Meningkatkan Kemampuan Pemahaman Konsep Matematika Siswa Menggunakan Model Pembelajaran Example dan Non Example - Aulia Rahmi; Ramdhan Witarsa; Iska Noviardila (Universitas Negeri Makassar, 2022)
This study aims to improve students' ability to understand mathematical concepts using example and non-example learning models. The research method used is the classroom action research method, with the steps of planning, implementing, observing, and reflecting. The research subjects were 27 students, consisting of 15 male students and 12 female students. Data collection techniques used are observation, tests, and documentation. The research instrument used was the teacher's activity observation sheet and the student's mathematical concept understanding test sheet. The results showed that there was an increase in students' ability to understand mathematical concepts from pre-action to cycle 1 by 1.23%. The increase in students' ability to understand mathematical concepts also occurred in cycle 1 to cycle 2 by 8.23%. The conclusion of this study is that the application of example and non-example learning models can increase students' ability to understand mathematical concepts as a whole by 9.46%. The example and non-example learning models need to be continued by the teacher because with the example and non-example learning models students become more active in participating in learning. The use of example and non-example learning models can facilitate the needs of elementary school students who are still thinking at a concrete operational level.